1996
DOI: 10.1063/1.118027
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectricity in gallium nitride thin films

Abstract: We report on the measurements of the pyroeffect in wurtzite n-type GaN films deposited over basal plane sapphire substrates. We measured the voltage drop between the contacts while the sample was subjected to the uniform heating or cooling. The pyroelectric voltage coefficient extracted from our data is comparable to that of the pyroelectric ceramics (∼104 V/m K). Our results show that the pyroelectric effect in GaN is a combination of a fast response to an initial heat flow and a slower response related to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 0 publications
3
44
0
3
Order By: Relevance
“…From the experimental data given in Ref. 15 , we estimated P v ~ 10 4 V/m-K. This value is close to the values of P v for pyroelectric ceramics, such as PZT and BaTiO 3 .…”
Section: Pyroelectricity In Gallium Nitride Thin Filmssupporting
confidence: 81%
See 3 more Smart Citations
“…From the experimental data given in Ref. 15 , we estimated P v ~ 10 4 V/m-K. This value is close to the values of P v for pyroelectric ceramics, such as PZT and BaTiO 3 .…”
Section: Pyroelectricity In Gallium Nitride Thin Filmssupporting
confidence: 81%
“…2) heating and cooling. 15 The time dependence of the voltage response in the GaN sample under applied temperature gradient is shown in Fig. 2.…”
Section: Pyroelectricity In Gallium Nitride Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Recently Bykhovski et al 9 reported experimental observations of pyroelectric response in thin films of gallium nitride that were ϳ10 4 V/m-K. Because AlN has larger piezoelectric coefficients than GaN, it is reasonable to expect, as suggested in Ref. 2 and 7, that the pyroelectric effect might be higher in AlN.…”
mentioning
confidence: 98%